2021
DOI: 10.1208/s12248-021-00576-y
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline-Induced Cardiotoxicity: Molecular Insights Obtained from Human-Induced Pluripotent Stem Cell–Derived Cardiomyocytes (hiPSC-CMs)

Abstract: Anthracyclines are a class of chemotherapy drugs that are highly effective for the treatment of human cancers, but their clinical use is limited by associated dose-dependent cardiotoxicity. The precise mechanisms by which individual anthracycline induces cardiotoxicity are not fully understood. Human-induced pluripotent stem cell–derived cardiomyocytes (hiPSC-CMs) are emerging as a physiologically relevant model to assess drugs cardiotoxicity. Here, we describe an assay platform by coupling hiPSC-CMs and imped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 19 publications
(16 reference statements)
4
11
0
Order By: Relevance
“…We measured LV-GLS and LV-GCS in this study and found that LV-GLS appeared more sensitive to LV-GCS in demonstrating early myocardial impairment induced by anthracyclines. LV-GLS in the anthracycline group began to decrease as early as cycle-2 of chemotherapy, and more significantly decline was noticed at cycle-4, which is consistent with the known dose-dependent myocardial toxicity of anthracyclines [ 20 ]. Patients undertook trastuzumab presented decreased LV-GLS and LV-GCS only at cycle-4, suggesting that early myocardial deformation may not change in a time-frame pattern in response to this type of agent.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We measured LV-GLS and LV-GCS in this study and found that LV-GLS appeared more sensitive to LV-GCS in demonstrating early myocardial impairment induced by anthracyclines. LV-GLS in the anthracycline group began to decrease as early as cycle-2 of chemotherapy, and more significantly decline was noticed at cycle-4, which is consistent with the known dose-dependent myocardial toxicity of anthracyclines [ 20 ]. Patients undertook trastuzumab presented decreased LV-GLS and LV-GCS only at cycle-4, suggesting that early myocardial deformation may not change in a time-frame pattern in response to this type of agent.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, similar to GLS, all MW parameters had gradual temporal changes in patients with anthracycline, but only GCW in patients with trastuzumab. The increase in GWW and decrease in other MW parameters over time in the anthracycline group probably result from the cumulative dose-dependent cardiotoxicity of type-I CTRCD [ 20 ]. MW related parameters are assumed loading-independent and mainly used to describe the dynamic changes noted in the myocardial strain along with the changes of LV pressure during the cardiac cycle, which may reflect myocardial work and metabolic demand [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…On day 7, the medium was replaced with RPMI1640 containing 2% B-27 supplement (Thermo Fisher Scientific; RPMI/B27), and cells were further cultured for an additional 2 weeks with RPMI/B27 changed every 3rd day. The cells used in the study were of maturation age: 25-35 days post-differentiation [64,65]. All cells were maintained in a humidified tissue culture incubator at 37 • C and 5% CO 2 .…”
Section: Differentiation Of Human Ipsc-derived Cardiomyocytesmentioning
confidence: 99%
“…pentamidine) (Dennis et al 2007 ; Obergrussberger et al 2016 ; Asahi et al 2019 ) and chemotherapeutic molecules (e.g. doxorubicin) (Kumar et al 2012 ; Chaudhari et al 2017 ; Mladěnka et al 2018 ; Narezkina and Nasim 2019 ; Bozza et al 2021 ) may not show their cardiotoxic effects after acute dose administration but may become toxic after repeated and prolonged exposures (several hours to days) (Cai et al 2019 ). Thus, adverse cardiac effects occurring after long-term drug exposure may be undetected during the preclinical screening and may allow for the further development of potentially toxic molecules.…”
Section: Introductionmentioning
confidence: 99%